Identification of Covariates Modulating B‐Cell Repopulation Kinetics in Subjects Receiving Rituximab Treatment - Welte, Thomas; Westermann, Lukas; Kappes, Julia; Schramm, Markus A.; Bemtgen, Xavier; Staudacher, Dawid L.; Hug, Martin J.; Venhoff, Nils; Arnold, Frederic (Arthritis & rheumatology (Hoboken, N.J.), 2023)
Effective B-cell depletion using the anti-CD20 monoclonal antibody rituximab is a cornerstone in the therapeutic concept of multiple autoimmune diseases. B-cell depletion is associated with a higher risk for severe infections and the timespan of B-cell repopulation differs greatly between individuals. Data on factors influencing B-cell repopulation kinetics are limited. This study aims to identify patient-specific and therapy-associated covariates that modulate B-cell repopulation. This single-center retrospective observational study presents data of 839 subjects receiving 2,017 courses of anti-CD20 antibody rituximab for auto-immune disease. Assessed covariates are patient-specific factors (sex, age, kidney function and underlying disease) and co-immunosuppression with common agents (azathioprine, cyclosporine A, cyclophosphamide, hydroxychloroquine, methotrexate, mycophenolate mofetil, tacrolimus and corticosteroids). The primary endpoint is the time to B-cell repopulation (CD19 cells ≥ 5/μl). The secondary endpoint is the time to B-cell reconstitution (CD19 cells ≥ 50/μl). Multivariate time-to-event analysis and logistic regression models were applied to estimate the influence of covariates. Age > 60 years (HR 0.71 for repopulation, P = 0.008), impaired kidney function (HR 0.72, P = 0.001), AAV (HR 0.61, P < 0.001), solid organ transplantation (HR 0.4, P < 0.001), and co-immunosuppression with corticosteroids (HR 0.64, P < 0.001) or azathioprine (HR 0.49, P < 0.001) were associated with impaired B-cell repopulation and reconstitution. The effects of corticosteroids (P = 0.043) and azathioprine (P = 0.025) were dose-dependent. Prolonged rituximab dosing intervals may be effective to achieve B-cell depletion and reduce risk of infection in advanced age or patients with impaired kidney function. Co-medication with corticosteroids or azathioprine prolongs B-cell recovery, which may increase therapeutic effects, but also the rate of adverse events.